Progress in modelling fast-ion D-alpha spectra and neutral particle analyzer fluxes using FIDASIM. (19th August 2020) - Geiger, B.; Stagner, L.; Heidbrink, W.W.; Dux, R.; Fischer, R.; Fujiwara, Y.; Garcia, A.V.; Jacobsen, A. S.; Jansen van Vuuren, A.; Karpushov, A. N.; Liu, D.; Schneider, P. A.; et al.
Abstract: FIDASIM is a code that models signals produced by charge-exchange reactions between neutrals and ions (both fast and thermal) in magnetically confined plasmas. With the ion distribution function as input, the code predicts the efflux to a neutral particle analyzer diagnostic and the photon radiance of Balmer-alpha light to a fast-ion D α diagnostic, in addition to many other related quantities. A new, parallelized version of the Monte Carlo code FIDASIM has been developed in Fortran90 that is substantially faster than the original interactive data language version. Modified algorithms include more accurate treatments of the time dependent collisional-radiative equations that describe neutral energy levels, of the cloud of 'halo' neutrals that surround the injected neutral beam, and of finite Larmor radius effects. Enhanced physics capabilities include modelling 'passive' signals from cold edge neutrals, the ability to treat general three-dimensional magnetic confinement configurations, and calculations of diagnostic-specific weight functions that enable tomographic reconstructions of the fast-ion distribution function. Neutral beam attenuation, beam emission, and fast-ion birth profiles are also modelled. The new algorithms have been successfully validated against experimental data and new features have been tested through benchmarks between two independently developed versions of the code.